2004
DOI: 10.1007/s00438-004-1031-7
|View full text |Cite
|
Sign up to set email alerts
|

Multiple transcripts of a gene for a leucine-rich repeat receptor kinase from morning glory (Ipomoea nil) originate from different TATA boxes in a tissue-specific manner

Abstract: TATA boxes are the most common regulatory elements found in the promoters of eukaryotic genes because they are associated with basal transcription initiation by RNA polymerase II. Often only a single TATA element is found in a given promoter, and tissue-, stage-and/or stimulus-specific expression occurs because the TATA box is associated with other cis -acting elements that enhance or repress transcription. We used software tools for gene analysis to assist in locating potential TATA box(es) in an AT-rich regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Today it is known that even if no consensus TATA‐box is identified in a promoter, TATA‐like boxes are found in many gene promoters that are associated with transcription initiation sites (Rhee and Pugh, ). Furthermore, different transcription initiation sites have been found associated with the presence of more than one TATA‐box in gene promoters that have several transcripts (Struhl, ; Yamada et al, ; Bassett et al, ; Grace et al, ; Farrell and Bassett, ; Bassett et al, ). The presence of more than one transcript for myostatin agrees with Gonzalez‐Cadavid et al (1998) who found the human myostatin gene produces three transcripts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Today it is known that even if no consensus TATA‐box is identified in a promoter, TATA‐like boxes are found in many gene promoters that are associated with transcription initiation sites (Rhee and Pugh, ). Furthermore, different transcription initiation sites have been found associated with the presence of more than one TATA‐box in gene promoters that have several transcripts (Struhl, ; Yamada et al, ; Bassett et al, ; Grace et al, ; Farrell and Bassett, ; Bassett et al, ). The presence of more than one transcript for myostatin agrees with Gonzalez‐Cadavid et al (1998) who found the human myostatin gene produces three transcripts.…”
Section: Discussionmentioning
confidence: 99%
“…Also, a longer 5′UTR sequence is inferred to be transcribed from the reported promoter region of the Chlamys farreri myostatin gene sequence in which three transcription initiation sites were reported by Hu et al (); but only one TATA‐box was identified 29 bp before the start site of the NCBI reported mRNA transcript (EU563852.2). Transcription of one or another transcript when more than one TATA‐box is present has been associated with gene expression regulation, either in a tissue specific form (Kumar et al, ; Yamada et al, ; Bassett et al, ), in response to stress (Struhl, ), or during specific developmental stages (Grace et al, ). In addition to the TATA‐box found in the 5′UTR of the long N. subnodosus myostatin transcript, the in silico analysis identified a uORF.…”
Section: Discussionmentioning
confidence: 99%
“…Our study revealed that two TATA boxes, one P-box and one I-box were located at the far upstream region of CYP736B transcripts, whereas two CAAT boxes and a G-box were located at the TSS1-containing region, and one W-box was located at the TSS2-containing region. Previous studies indicated that TATA boxes are the most common regulatory elements found in promoters of eukaryotic genes because they are associated with basal transcription initiation by RNA polymerase II, especially with cis -acting elements that enhance or repress transcription [ 26 ]. I-box (core sequence GATAA) and P-box (core sequence TGTAAAG) were associated with light and ABA responsiveness in tobacco and Arabidopsis respectively [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…, 2001). Plants are not uncommon to this phenomenon, because multiple transcripts were alternatively transcribed from multiple TATA boxes in a tissue‐specific manner for a gene encoding leucine‐rich repeat receptor kinase in Ipomoea nil (Bassett et al. , 2004).…”
Section: Introductionmentioning
confidence: 99%